Firefly's world of facts - Ash, Russell (Richmond Hill, Ont. : Firefly Books, 2007)
Presents a collage of information about science, history, culture, and human civilization
Includes index
Keywords: Curiosities and wonders; Handbooks, vade-mecums, etc; Curiosites et merveilles; Guides, vade-mecum, etc; Handbooks, manuals, etc; Curiosities and wonders